Singgah Sahur UMP for orphans and security agencies - Mimi Rabita, Abdul Wahit (2023)
KUANTAN, April 15, 2023 - Universiti Malaysia Pahang (UMP) spent time with 41 orphans at the Hembusan Kasih Sayang Care Centre in Taman Guru and met frontliners at the Kuantan Fire and Rescue Station and Indera Mahkota Police Station to distribute sahur meals.